Double-layer effect on the kinetics of CO2 electroreduction at cathodes bearing Ag, Cu, and Ag/Cu nano-arrays electrodeposited by potentiostatic double-pulse. (October 2018) - Banda-Alemán, Jorge A.; Orozco, G.; Bustos, E.; Sepúlveda, S.; Manríquez, J.
Graphical abstract: Highlights: In-doped SnO2 cathodes bearing Ag, Cu and bimetal Ag/Cu nanoparticulate arrays were prepared by potentiostatic double-pulse technique. These cathode systems were employed for studying the multi-step charge-transfer kinetics of CO2 electrochemical reduction in propylene carbonate solutions. Current exchange density of CO2 electrochemical reduction at rate-determining step depends in large part on the values achieved by the outer-Helmholtz plane potential for the three cathode systems that we explored. Individual electrocatalytic properties of Ag and Cu were successfully coupled when deposited in a bimetallic array to intentionally tune the CO2 electrochemical reduction rate in propylene carbonate. Abstract: In-doped SnO2 (ITO) cathodes bearing Ag, Cu and bimetallic Ag/Cu nanoparticulate arrays (cathode systems ITO//Ag, ITO//Cu and ITO//Ag/Cu, respectively) were prepared by a potentiostatic double-pulse technique and employed for studying the multi-step charge-transfer kinetics of CO2 electrochemical reduction (CO2 ER) in propylene carbonate solution. Our results demonstrated, on one hand, that the current exchange density of the rate-determining step ( rds ) for the CO2 electrochemical reduction ( io, rds ) depends, predominantly, on the values achieved by the outer-Helmholtz plane (OHP) potential (ΔψOHP, rds ) on the three cathode systems here explored. Furthermore, these results showed that a large ΔψOHP, rds (−647 mV) promoted a large io, rds (1.09 × 10 −2 A⋅ cm −2 ) for CO2 reduction at the cathode system ITO//Cu, whereas a small ΔψOHP, rds (−168 mV) produced a small io, rds (2.05 × 10 −4 A⋅ cm −2 ) for CO2 reduction at the cathode system ITO//Ag. In contrast, intermediate values of ΔψOHP, rds and io, rds (−333 mV, 1.09 × 10 −3 A⋅ cm −2 ) were found for CO2 reduction on the cathode system ITO//Ag/Cu, demonstrating that the individual electrocatalytic properties of Ag and Cu can be coupled in a bimetallic array to intentionally tune the CO2 ER rate in nonaqueous solvents having low proton availability.